Pomegranate‐Inspired Graphene Parcel Enables High‐Performance Dendrite‐Free Lithium Metal Anodes - Long Zhang; Tao Ma; Yi‐Wen Yang; Yi‐Fei Liu; Peng‐Hu Zhou; Zhao Pan; Bi‐Cheng Hu; Chuan‐Xin He; Shu‐Hong Yu (Advanced Science, 2022)
Abstract Uncontrolled lithium dendrites seriously hinder the commercialization of lithium metal batteries in comparison to the durable lithium‐ion batteries. Herein, inspired by squashy pomegranate structure, a novel loading strategy of metallic lithium (Li) is introduced to construct dendrite‐free Li metal anodes through porous reduced graphene oxide/Au (PRGO/Au) composite microrods (MRs) as unique storage parcels. The abundant internal voids and robust host structure are capable of achieving high mass loading of Li metal and effectively alleviating the conceivable volume change during cycling, accompanied by the preferential selective plating/stripping of Li inside the graphene‐based MRs with the embedded Au nanonuclei. As a result, the obtained PRGO/Au–Li anodes deliver a long‐lifespan stable cycling up to 600 h with a high specific capacity of ≈2140 mA h g–1 and voltage hysteresis as low as 20 mV in the absence of dendrites. The assembled full cells exhibit excellent rate capability and cycling stability. This work provides an alternative strategy to construct advanced high‐energy‐density lithium batteries via the unique 1D bioinspired graphene‐based packaging strategy.